Can we truly rely on the urinary antigen test for the diagnosis? Legionella case report. (13th April 2017) - Miyata, Jun; Huh, Ji Young; Ito, Yukiko; Kobuchi, Taketsune; Kusukawa, Kazuko; Hayashi, Hiroyuki
Abstract: It is critical to diagnose and treat Legionella pneumonia (LP) immediately after infection because of the associated high mortality. The urine antigen test (UAT) is often used for the diagnosis of LP; however, it cannot detect the serogroups of all Legionella species. A detained medical history and several clinical findings such as liver enzyme elevation and hyponatremia are useful in diagnosis. Some specific types of Legionella are found in compost. Herein, we report a case of LP in which the patient's medical history and several clinical findings were useful for diagnosis.